Effectiveness of Organic Waste Degradation Level using the Black Soldier Fly Maggot - Mufid Dahlan; Wahyuni; Anik Fadlilah; Sani Rusminah; Muhammad Chusnul Khitam; Yulia Putri Yani; Elly Ahsan; Rosyad Haqiqi; Marsha Savira Agatha Putri (Journal of Health Science and Prevention, 2023)
Sekaran Village is a village with a dense population, so the quantity of waste, both organic and inorganic from the village community is also high. This experiment focuses on processing organic waste only with Maggot Black Soldier Fly (BSF) media which has the potential to decompose organic waste. The purpose of this study was to determine the level of degradation of organic waste with BSF maggot media at the Sekar Benefit 3R Temporary Disposal Site (TPS) Sekaran District, Lamongan Regency. The results of this experiment include the increase in the mass of Baby Maggot BSF before and after degrading waste. The level of degradation of organic waste with Baby Maggot BSF is rice (69.83%), bones (50.5%), meat (46%), fruit (45.83%), wet leaves (31.5%) and the last is dry leaves (16.67%). Meanwhile, the level of degradation of organic waste with Adult BSF Maggot is not as high as the level of degradation of organic waste with Baby Maggot BSF media. Organic waste type which easily degraded by Adults Maggot BSF for 24 hours are meat, fruit and rice up to 0.59, 0.44 and 0.11 kg. Meanwhile, dry leaves, wet leaves and vegetables, which were degraded up to 0.69, 0.59 and 0.7 kg. It was concluded that the type of organic waste did not affect the quantity of Adult BSF Maggot before and after degrading organic waste.